2011
DOI: 10.1111/j.1439-0426.2011.01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glutamine supplementation improves growth performance and intestinal digestion/absorption ability in young hybrid sturgeon (Acipenser schrenckii ♀ × Huso dauricus♂)

Abstract: Exogenous glutamine (Gln) was evaluated for its effect on growth performance, intestinal structure and function in young hybrid sturgeon (Acipenser schrenckii $ · Huso dauricus #). Seven basal diets supplemented with 0, 1.00% AlanylGlutamine (Aln-Gln, 63.02% Gln) and 1.00, 2.00, 3.00, 4.00, 5.00% Solpro 508 (30.04% Gln) (0.30, 0.60, 0.90, 1.20, 1.50 of Gln) were fed to fish (initial mean weight: 22.38 ± 0.18 g) for 8 weeks, Water temperature was 22.4 ± 1.0°C, Dissolved oxygen was 7.56 ± 0.76 mg L )1 , the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
2
23
0
3
Order By: Relevance
“…For instance, in red drum (Sciaenops ocellatus), although growth was not improved, feed efficiency was enhanced in Gln supplemented diets (Cheng et al, 2011). In hybrid striped bass (Morone chrysops × Morone saxatilis; Cheng et al, 2012), hybrid sturgeon (Qiyou et al, 2011) and Jian carp (Yan and Qiu-Zhou, 2006) both feed utilization and weight gain improvements were reported with dietary Gln supplementation. These apparently conflicting results are not exclusive to fish (Lobley et al, 2001) and seem to reveal species specific physiological differences that still need to be fully understood (Pohlenz et al, 2012a).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For instance, in red drum (Sciaenops ocellatus), although growth was not improved, feed efficiency was enhanced in Gln supplemented diets (Cheng et al, 2011). In hybrid striped bass (Morone chrysops × Morone saxatilis; Cheng et al, 2012), hybrid sturgeon (Qiyou et al, 2011) and Jian carp (Yan and Qiu-Zhou, 2006) both feed utilization and weight gain improvements were reported with dietary Gln supplementation. These apparently conflicting results are not exclusive to fish (Lobley et al, 2001) and seem to reveal species specific physiological differences that still need to be fully understood (Pohlenz et al, 2012a).…”
Section: Discussionmentioning
confidence: 80%
“…In hybrid sturgeon (Acipenser schrenckii × Huso dauricus). Gln supplementation was reported to enhance weight gain, feed efficiency, and intestine structure and function (Qiyou et al, 2011). In Jian carp (Cuprinus carpio var.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experiment showed that cultured Japanese eel's testicular fragments exposed to taurine in the medium showed higher SOD activities (Higuchi et al, 2012). On the other hand, dietary Gln was reported to enhance the antioxidant enzyme activities in hybrid sturgeon (Qiyou et al, 2011;Wang et al, 2011). Gln was also found to be effective in protecting against oxidative stress in carp intestinal epithelial cells by reducing malondialdehyde level and preventing the decrease of duperoxide dismutase activity (Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Park et al (2002) reported that dietary taurine level can alter the growth performance of juvenile Japanese flounder significantly, and the optimal dietary taurine level is 1.4% for the species. The effect of dietary Gln on Japanese flounder has not yet been reported, however it was reported that proper supplementation of Gln in diet can affect the growth performance of Jian carp (Lin and Xiao, 2006), red drum (Cheng et al, 2012) and hybrid sturgeon (Qiyou et al, 2011). In the present study, growth parameters increased when both dietary Tau and Gln levels increased, this might be partly explained by the increased trend of feed utilizations, which is consistent with previous studies on Tau in Japanese flounder and juvenile turbot separately (Kim et al, 2007;Qi et al, 2012) as well as Gln in Jian carp (Lin and Xiao, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in this research the maximum level of RPC inclusion in sturgeon diet was 53 % and at this level the dietary protein was almost completely RPC protein. Even if we decided to not analyze productive results, we interestingly observed that the specific growth rate (SGR) was 5 times better than the case of white sturgeon (A. transmontanus) (Gawlicka et al, 2002), and the productive parameters were also better than Beluga sturgeon (Hosseini et al, 2010;Ta'ati et al, 2011), "AL" hybrid sturgeon , hybrid sturgeon (Acipenser schrenckii x Huso dauricus) (Qiyou X. et al, 2011) and white sturgeon (Lin et al, 1997).…”
Section: Discussion Diets and Fish Growthmentioning
confidence: 98%